Ultrafast nonlinear optical properties and carrier dynamics of silver nanoparticle-decorated ZnO nanowires. Issue 46 (20th July 2018) - Zhang, Ke-Xin; Yao, Cheng-Bao; Wen, Xing; Li, Qiang-Hua; Sun, Wen-Jun
Abstract : Silver (Ag) nanoparticle-decorated zinc oxide (ZnO) nanowires (Ag–ZnO) have been successfully synthesized by chemical vapour deposition and the magnetron sputtering method. Abstract : Silver (Ag) nanoparticle-decorated zinc oxide (ZnO) nanowires (Ag–ZnO) have been successfully synthesized by chemical vapour deposition and the magnetron sputtering method. Scanning electron microscopy images indicate that Ag nanoparticles are distributed uniformly on the surface of the ZnO nanowires. The results of room temperature photoluminescence (RTPL) reveal two major emission peaks for the Ag–ZnO nanowires, and the emission peaks in the visible region are stronger than those of the unmodified ZnO nanowires. The mechanism of RTPL and low temperature photoluminescence (LTPL) emission is discussed in detail. Nonlinear optical properties and ultrafast dynamics have been investigated using the Z -scan and two color pump–probe (TCPP) techniques, respectively. The nonlinear absorption properties in the nano-, pico- and femto-second regime have been analyzed using the singlet state three-level and four-level models, respectively. The samples show self-focusing nonlinearity and good two-photon absorption (TPA)-induced ground state saturation absorption as well as excited state reverse saturable absorption behavior. For the nanosecond and picosecond pulses, the reverse saturated absorption in the excited state mainly originates from the absorption at low excited states or deep levels; however, for the femtosecond pulse, it is caused by the absorption at high excited states. The TCPP results show that the ground state or deep level light bleaching (for nano- and pico-second regime) and TPA-induced excited-state absorption (for femtosecond regime) behaviors range from 470 nm to 620 nm. The remarkable nonlinear optical properties reveal that Ag–ZnO nanowires are potential nanocomposite materials for the development of nonlinear optical devices.